2007
DOI: 10.1007/s00401-007-0257-y
|View full text |Cite
|
Sign up to set email alerts
|

Pathological TDP-43 in parkinsonism–dementia complex and amyotrophic lateral sclerosis of Guam

Abstract: Pathological TDP-43 is the major disease protein in frontotemporal lobar degeneration characterized by ubiquitin inclusions (FTLD-U) with/without motor neuron disease (MND) and in amyotrophic lateral sclerosis (ALS). As Guamanian parkinsonism-dementia complex (PDC) or Guamanian ALS (G-PDC or G-ALS) of the Chamorro population may present clinically similar to FTLD-U and ALS, TDP-43 pathology may be present in the G-PDC and G-ALS. Thus, we examined cortical or spinal cord samples from 54 Guamanian subjects for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
119
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 162 publications
(125 citation statements)
references
References 35 publications
6
119
0
Order By: Relevance
“…These TDP-43 inclusions were distinct from the tau pathology in the spinal cord. Interestingly, TDP-43 pathology was also detected in cortical and limbic regions from Guam-PDC cases, inclusions that were not detected with antibodies to the tau protein [40,41]. Thus, these results support the hypothesis that ALS and FTLD-U represent a clinical spectrum of neurodegenerative disease characterized by TDP-43 pathology (Fig.…”
Section: Tdp-43 Pathology In Ftld-u and Alssupporting
confidence: 79%
See 2 more Smart Citations
“…These TDP-43 inclusions were distinct from the tau pathology in the spinal cord. Interestingly, TDP-43 pathology was also detected in cortical and limbic regions from Guam-PDC cases, inclusions that were not detected with antibodies to the tau protein [40,41]. Thus, these results support the hypothesis that ALS and FTLD-U represent a clinical spectrum of neurodegenerative disease characterized by TDP-43 pathology (Fig.…”
Section: Tdp-43 Pathology In Ftld-u and Alssupporting
confidence: 79%
“…Consistent with these findings is the reported absence of TDP-43 immunoreactivity in inclusions in mutant SOD1 (G93A) transgenic mice [39]. In contrast, in Guam ALS and parkinsonism-dementia complex (PDC), a disease of unknown etiology affecting the Chamorro populations and characterized by extensive tau pathology, TDP-43 inclusions were detected in the spinal cord of both ALS and PDC cases but not in controls [40]. These TDP-43 inclusions were distinct from the tau pathology in the spinal cord.…”
Section: Tdp-43 Pathology In Ftld-u and Alssupporting
confidence: 56%
See 1 more Smart Citation
“…Studies have focused on the role of neurotoxicity of sterol glucosides found in the seeds of Cycas circinalis that are part of the diet in Guam (2) and on the neurotoxin ␤-methylamino-alanine found in cyanobacteria (3). The spinal cords of ALS patients are characterized by pathological accumulation of sphingomyelin, ceramides, and cholesterol esters (4), which are thought to sensitize motor neurons to programmed cell death and cytoplasmic accumulation of aggregates of ubiquitin and transactivation response DNA-binding protein (TDP-43) (5,6).…”
mentioning
confidence: 99%
“…The other school favored the idea that ALS on Guam was an independent disease process similar to ALS that occurred in other settings [18]. The relative specificity of TDP-43 has been used to study ALS than occurs on Guam in the study by Geser and co-workers in this issue of Acta Neuropathologica [7]. Spinal cord pathology was studied in a group of cases of ALS, PDC and normal controls from Guam.…”
mentioning
confidence: 99%